2015
DOI: 10.1007/s10508-015-0528-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender Atypicality and Anxiety Response to Social Interaction Stress in Homosexual and Heterosexual Men

Abstract: Gender non-conforming behavior and a homosexual sexual orientation have both been linked to higher levels of anxiety. This study examined the independent and interactive effects of gender atypicality and sexual orientation on levels of state anxiety immediately following a stressful social interaction task among a sample of homosexual and heterosexual Israeli men (n = 36). Gender atypicality was measured via both self-report and observer ratings. State anxiety was measured via both self-report immediately subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 74 publications
0
8
0
1
Order By: Relevance
“…Believing voice as a SO-trait is immutable and discrete was expected to relate to LG participants' perceptions of sounding less gender typical, confirming common stereotypes (path d and e; Hypothesis 5a), whilst controllability beliefs were expected to be associated with higher perceptions of sounding gender typical (path f; Hypothesis 5b). Self-perceptions of gender-atypical traits have been found to trigger stress (Jacobson, Cohen, & Diamond, 2016;Martin-Sotrey & August, 2016) and internalized stigma (Salvati, Pistella, & Baiocco, 2018), and to be relevant for wellbeing (Rieger & Savin-Williams, 2012). Thus, we predicted that sounding less gender typical would be related to more rejection expectancy and vigilance (path i and j; Hypothesis 6).…”
Section: Studymentioning
confidence: 87%
“…Believing voice as a SO-trait is immutable and discrete was expected to relate to LG participants' perceptions of sounding less gender typical, confirming common stereotypes (path d and e; Hypothesis 5a), whilst controllability beliefs were expected to be associated with higher perceptions of sounding gender typical (path f; Hypothesis 5b). Self-perceptions of gender-atypical traits have been found to trigger stress (Jacobson, Cohen, & Diamond, 2016;Martin-Sotrey & August, 2016) and internalized stigma (Salvati, Pistella, & Baiocco, 2018), and to be relevant for wellbeing (Rieger & Savin-Williams, 2012). Thus, we predicted that sounding less gender typical would be related to more rejection expectancy and vigilance (path i and j; Hypothesis 6).…”
Section: Studymentioning
confidence: 87%
“…Participants were exposed to a TSST modified to ensure maximisation of sex differences in stress response (the panel were placed behind a one-way mirror; this is associated with reduced HPA axis response compared to standard TSST in heterosexual females but not males). However, another study did not find an impact of sexual orientation on salivary cortisol in men ( Jacobson et al., 2016 ). Sexual orientation may exert a greater influence in regions where social stigma towards homosexuality is particularly high; structural stigma (operationalised using factors such as level of exclusion of homosexual people from social institutions) was associated with a blunted response to the TSST in homosexual and bisexual young adults ( Hatzenbuehler and McLaughlin, 2014 ).…”
Section: Studies In Males and Femalesmentioning
confidence: 88%
“…Contradicting results were seen in that some studies found significant differences in the levels of cortisol between self-identified heterosexuals and LGB and unsure populations. Other studies found that cortisol levels were not significantly different and depended more on other factors such as race, ethnicity, gender, or level of stigmatization (Austin et al, 2016; Cook, Juster, Calebs, Heinze, & Miller, 2017; Hatzenbuehler et al, 2014; Jacobson, Cohen, & Diamond, 2016; Juster et al, 2013, 2015). The current study adds to the existing literature by including ninth-grade high school students in a comparison study of self-identified heterosexuals with LGB and unsure students.…”
mentioning
confidence: 90%